2019
DOI: 10.1088/1755-1315/348/1/012131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biofloc density and crude protein level in the diet on the growth performance, survival rate, and feed conversion ratio of Black Tiger Prawn (Penaeus monodon)

Abstract: The objectives of the present study were to evaluate the best combination of biofloc density in culture media and percentage crude protein content on feed on growth performance, survival rate and feed utilization of the black tiger shrimp (Penaeus monodon) culture system. The Completely Factorial Random Design (CFRD) was used in this study. The first tested factor is the percentage of crude protein in the diet at three levels namely; 35%, 30%, 25%, and the second factor is biofloc density at in three levels na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
2
0
3
Order By: Relevance
“…Some authors (Ferreira et al, 2017; Hapsari, 2016; Hu et al, 2017; Miao et al, 2017) underline the importance of biofloc in aquaculture systems, because they decrease susceptibility to diseases and increase digestive efficiency. Supriatna et al (2019) obtained 100% survival of tiger shrimp ( Penaeus monodon ) in treatments with biofloc, associated with less stress and efficient use of nutrients. Ekasari et al (2021) cultured prawns in biofloc and observed a higher weight (36%) compared to the control group, which was attributed to the nutritional contribution of the biofloc.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors (Ferreira et al, 2017; Hapsari, 2016; Hu et al, 2017; Miao et al, 2017) underline the importance of biofloc in aquaculture systems, because they decrease susceptibility to diseases and increase digestive efficiency. Supriatna et al (2019) obtained 100% survival of tiger shrimp ( Penaeus monodon ) in treatments with biofloc, associated with less stress and efficient use of nutrients. Ekasari et al (2021) cultured prawns in biofloc and observed a higher weight (36%) compared to the control group, which was attributed to the nutritional contribution of the biofloc.…”
Section: Discussionmentioning
confidence: 99%
“…Parameter kualitas air pada pemeliharaan ikan nila merah pada sistem bioflok dengan frekuensi pakan yang berbeda memperlihatkan kisaran yang optimal untuk pertumbuhan dan sintasam ikan. Penerapan teknologi bioflok merupakan alternatif untuk mengatasi masalah kualitas air dalam kegiatan budidaya dan untuk mengatasi dampak negatif limbah akuakultur terhadap lingkungan (Nurhatijah et al, 2016;Zulfahmi et al, 2018;Supriatna et al, 2019). Kualitas air pada penelitian ini disajikan pada Tabel 2.…”
Section: Hasil Dan Bahasanunclassified
“…Amonia (NH 3 ) dalam media pemeliharaan berasal dari pakan yang tidak termakan, selanjutnya berubah menjadi nitrit (NO 2 ) dan nitrat (NO 3 ) melalui proses nitrifikasi (Azim & Little, 2008;Stein & Klotz, 2016). Aplikasi bioflok pada sistem budidaya ditujukan untuk pengelolaan kualitas air dan mengatasi pengaruh buruk terhadap lingkungan akibat limbah budidaya (Supriatna et al, 2019).…”
Section: Hasil Dan Bahasanunclassified
“…Salah satu bakteri heterotrof yang mendominasi sistem biofloc adalah Bacillus (Kasan et al, 2017). Keuntungan dari teknologi biofloc ini antara lain: mempertahankan kualitas air (Avnimelech, 2009;Nurhatijah et al, 2016), sebagai pakan alami sehingga dapat mengurangi kebutuhan pakan komersil (Supono et al, 2014;Supriatna et al, 2019), serta keberadaan bakteri heterotrof dapat menekan pertumbuhan Vibrio (Crab et al, 2012) dan meningkatkan imunitas nonspesifik udang (Panigrahi et al, 2018). Sistem biofloc juga mampu meningkatkan efisiensi penggunaan nitrogen dan fosfor pada pakan udang tambak intensif (Da Silva et al, 2013).…”
Section: Pendahuluanunclassified